2020
DOI: 10.1177/0963689720939127
|View full text |Cite
|
Sign up to set email alerts
|

NOD Mice—Good Model for T1D but Not Without Limitations

Abstract: The nonobese diabetic (NOD) mouse model of type 1 diabetes (T1D) was discovered by coincidence in the 1980s and has since been widely used in the investigation of T1D and diabetic complications. The current in vivo study was originally designed to prospectively assess whether hyperglycemia onset is associated with physical destruction or functional impairment of beta cells under inflammatory insult during T1D progression in diabetes-prone female NOD mice. Prediabetic 16- to 20-wk-old NOD mice were transplanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…By 30 weeks of age, 77% of the mice were diabetic. Overall, the incidence of diabetes in female NOD mice in our study was somewhat less than reported [ 27 30 ]. This may be due to presence of Salmonella or other environmental factors [ 29 , 32 ].…”
Section: Discussioncontrasting
confidence: 72%
“…By 30 weeks of age, 77% of the mice were diabetic. Overall, the incidence of diabetes in female NOD mice in our study was somewhat less than reported [ 27 30 ]. This may be due to presence of Salmonella or other environmental factors [ 29 , 32 ].…”
Section: Discussioncontrasting
confidence: 72%
“…The most common T1DM model, the NOD mouse, is prone to spontaneously developing autoimmune diabetes, which mimics many features of human disease such as, islet infiltration by immune cells (insulitis) and the development of autoantibodies [ 61 , 68 , 69 ]. It has been subjected to numerous successful experimental interventions, a majority of which have later failed in human clinical trials [ 68 ].…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…The most common T1DM model, the NOD mouse, is prone to spontaneously developing autoimmune diabetes, which mimics many features of human disease such as, islet infiltration by immune cells (insulitis) and the development of autoantibodies [ 61 , 68 , 69 ]. It has been subjected to numerous successful experimental interventions, a majority of which have later failed in human clinical trials [ 68 ]. Nonetheless, the number of similarities of human T1DM pathophysiology is astonishing, including similar polymorphisms that confer disease risk and the involvement of similar genes or biological pathways on the disease’s onset as well as immune response [ 68 , 70 ].…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…In NOD/ SCID mice, the SCID mutation (severe combined immunodeficiency) is combined with the NOD type (non-obese diabetic). SCID mutation homozygous animals do not form any T-or B-cells (with preserved myelopoiesis), and myeloid cells and natural killer (NK) cells functions can also be restricted In NOD mice, diabetes is caused by autoimmune reactions that cause the destruction of insulin-producing beta cells (Aldrich et al, 2020). Furthermore, polymorphisms of the Idd3 locus exist, that lead to increased IL-2 (IL ¼ interleukin) and IL-21 levels, which can influence the function of dendritic cells, B-cells, T-cells, and NK-cells (Wendt et al, 2007), and a mutation of the CTLA-4 gene (cytotoxic T-lymphocyteassociated Protein 4) results in an attenuated T-cell immune response (Ueda et al, 2003).…”
Section: Xenograft and Syngeneic Modelsmentioning
confidence: 99%